Dietary intake of young portuguese handball players - Sá, Carla (2022)
The aim of this study was to analyse dietary intake (macronutrients and micronutrients) in young female and male handball athletes. A transversal study was performed with young handball players from sub 16 and 18 Portuguese Handball Federation, who volunteered to participate in this study. Anthropometric (weight and height measure), nutritional intake (using food frequency questionnaire) and position in the game were evaluated. The final sample comprised 64 athletes (48.4% female and 51.6% male). The mean age was 16± 1 years, average body mass index was higher in females (24.1± 3.5kg/m2) than males (23.8± 3.0 kg/m2). Mean energy intake per day was significantly lower in females than males 2167.4± 1185.0 and 2952.9± 1315.8 kcal/day (p= 0.015, 95CI), respectively. According to the recommendations from food, most of the young handball athletes reported a generally higher dietary intake (protein intake was near to the upper recommendation limit; the carbohydrate intake was below and the fat intake higher) and a lower for some micronutrients. A process to identify the athletes that need nutritional support should be considered by handball coaches to optimise their performance and safeguard their health.